Utilization Of Wavepad Application On Learning Istima ' In Madrasah Tsanawiyah PSA Sulit Air Class VII: Pemanfaatan Aplikasi Wavepad Pada Pembelajaran Istima’ Di Madrasah Tsanawiyah PSA Sulit Air Kelas VII - Adam Mudinillah; Amrina Amrina; Nur Afni Oktavia (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2021)
Current technological developments can bring changes in all sectors, such as in the education sector which can make it easier for an educator to transfer their knowledge through the media used in Arabic language learning. The process of transferring knowledge is usually done face-to-face, but because of these changes and developments, the process of delivering knowledge is done virtually through learning media. Wavepad is one of the media that can be accessed by educators to facilitate the learning process that can improve the skills of an educator through the media he developed. An educator can also develop a mindset through these media. The method used in this study is a qualitative method, which in this method is carried out by conducting interviews with these students and analyzing and collecting student data in MTS PSA Sulit Air. The indicator that can be successful from this research is to add insight into what is being studied in educational institutions. The results obtained from this research activity are that researchers can develop new insights and ideas so that they can come up with creative ideas. The researcher also hopes that educators can take advantage of the wavepad application in Arabic language learning, especially for maharah istima 'which is liked by students, and students can be enthusiastic about participating in the learning process.